Calvyn se leer oor die kerk 1 - Botha, Schalk Jacobus (Hervormde teologiese studies, 2000)
Calvin's doctrine concerning the church. A few aspects of Calvin's teachings on the church are pointed out to encourage the two churches involved in the Hervormde Theological Training to reconsider what Calvin himself has to say. This should not be done only in the ligth of his role in the past, but also within the context of the tremendous challenges and responsibilities that these two churches will have to face in the next millennium. Calvin's doctrine on the church can still provide instruction and guidance to the church today.